Factors associated with adolescent pregnancy in selected rural municipalities of Lalitpur district: A mixed method study - Bhatta, Kusumsheela; Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Introduction: Adolescent pregnancy increases the vulnerability to life threatening consequences in terms of developmental, sexual and reproductive health. This study aimed to find factors associated with adolescent pregnancy in selected rural municipalities of Lalitpur district using mixed methods approach.Method: Cross sectional study was conducted among 30 adolescent mothers, selected purposively, from Bagmati and Konjyosom Rural Municipality of Lalitpur district. 4 in-depth interviews and 2 key informant interviews were taken for qualitative study. Concurrent mixed-method triangulation design was used. Fisher’s exact test was used to find risk factors whereas Braun and Clarke’s six-step thematic analysis based on socio-ecological model themes was used to explore the reasons of adolescent pregnancy. Results from quantitative and qualitative findings were triangulated.Result: Out of 30 participants, 15(50%) participants had adolescent pregnancy. Family type, marriage type, age at marriage and unplanned pregnancy were significantly associated with adolescent pregnancy. Many risk factors were identified at different socio-ecological level from qualitative analysis. The results from triangulation of findings identified early marriage, marriage by elopement, unplanned pregnancy and perception regarding contraceptives as convergent risk factor, ethnicity as divergent risk factors and health workers behavior, laws, marriage and pregnancy norms, family pressure, access to media and decision making level as expansion risk factors.Conclusion: Preventing adolescent pregnancy calls for multifaceted measures at different socioecological level that are focused on the empowerment of girls with interventions tailed to particular subgroups especially the most vulnerable and marginalized ones.